Moisture flux and vergence of water vapour over India during drought and good monsoons - RAO, GAPPA (MAUSAM, 1985)
Water vapour flux and vergence of moisture during drought and good monsoon seasons over India have been computed. The net moisture vergence over the country have been obtained. The diurnal variations in the fluxes and vergence based on 00 and 12 GMT observations have been evaluated. The contrasting features between the two years are discussed.